Effects of Variations in Ligand Density on Cell Signaling. Issue 39 (20th August 2015) - Satav, Tushar; Huskens, Jurriaan; Jonkheijm, Pascal
<x xml:space="preserve">Abstract</x> Multiple simultaneous interactions between receptors and ligands dictate the extracellular and intracellular activities of cells. The concept of programmable ligand display is generally used to study the interaction between ligands, displayed on surfaces at various densities, with receptors present on cell surfaces. Various strategies are discussed here to display ligands on surfaces to study their effect on cell behavior. Only very few strategies have been reported where this display combines precise control over density with lateral spacing of ligands on surfaces. In this review, selected examples of strategies to control ligand density and spacing and their implications for biological functions of cells are discussed.